SEPAKBOLA DAN ARGENTINA: CAMPUR TANGAN KOMUNIKASI STRATEGIS DALAM PEMBENTUKAN IDENTITAS BANGSA MELALUI LAPANGAN HIJAU - Andretty, Julian; Mulyaman, Darynaufal; Jonathan, Hans; Sasongko, Singgih (Universitas Nahdlatul Ulama Kalimantan Timur, 2025)
Football significantly shapes Argentina's national identity, making it more than a sport. This article explores the close relationship between football and the identity of the Argentine nation, tracing its development from the early days of football in the country to its transformation into a cultural symbol and source of national pride. The study analyzed how football, through its players, clubs, and historic moments, reflects Argentina's social, political, and cultural dynamics. A qualitative approach was employed in this study, with historical and cultural analysis as the primary methods. Data sources include academic literature and media documentation. The findings reveal that football serves as a medium for collective expression, particularly in the context of class struggles and political conflicts. The success of the national team, such as winning the World Cup, is not merely a sporting event but also a milestone in fostering national solidarity. Moreover, figures like Diego Maradona and Lionel Messi have become symbols of hope and aspiration for the Argentine people. This article contributes to a multidisciplinary understanding of football’s role in shaping national identity in developing countries. The findings are relevant to cultural studies, the sociology of sports, and political science, and can serve as a model for analyzing similar relationships in other nations. Thus, this article reinforces the argument that football transcends the boundaries of sport, becoming an integral element of Argentina's national identity narrative.